2001
DOI: 10.1159/000046833
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Changes in the Auditory Cortex of Congenitally Deaf Cats following Cochlear Implantation

Abstract: Congenitally deaf cats were used as a model for human inborn deafness and auditory deprivation. The deaf cats were supplied with a cochlear implant, chronically exposed to an acoustic environment and conditioned to acoustic stimuli. In case of early implantation the cats learned to make use of the newly gained auditory channel behaviourally. Neurophysiological and fMRI data showed that the central auditory system was recruited, if implantation took place within a sensitive period of <6 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 14 publications
1
37
0
Order By: Relevance
“…For example, inputs to layers III/IV of A1 are present in congenitally deaf animals, as are subsequent inputs to more superficial, supergranular layers (Klinke et al, 1999). However, activity in deeper, infragranular layers is significantly decreased (Kral et al, 2000, 2002), and synaptic current latencies are significantly longer [after controlling for brainstem latency shifts (Kral et al, 2000; Klinke et al, 2001)], suggesting that connections between superficial and deeper layers do not mature. In hearing animals, the infragranular layers of A1 are the source of descending, feedback projections.…”
Section: Effects Of Deafness On the Auditory Systemmentioning
confidence: 99%
“…For example, inputs to layers III/IV of A1 are present in congenitally deaf animals, as are subsequent inputs to more superficial, supergranular layers (Klinke et al, 1999). However, activity in deeper, infragranular layers is significantly decreased (Kral et al, 2000, 2002), and synaptic current latencies are significantly longer [after controlling for brainstem latency shifts (Kral et al, 2000; Klinke et al, 2001)], suggesting that connections between superficial and deeper layers do not mature. In hearing animals, the infragranular layers of A1 are the source of descending, feedback projections.…”
Section: Effects Of Deafness On the Auditory Systemmentioning
confidence: 99%
“…In agreement with this view, there is a growing body of electrophysiological evidence from studies in profoundly deaf animals that chronic ICES can result in changes in central auditory system response characteristics (for review see Fallon et al, 2008), and that this plasticity can in part ameliorate the effects of deafness on these responses. Such changes have been described both in the midbrain nucleus, the inferior colliculus (IC, e.g., Snyder et al, 1990, 1995; Vollmer et al, 1999, 2005) and in the primary auditory cortex (AI, e.g., Dinse et al, 1997, 2003; Fallon et al, 2009; Klinke et al, 2001; Kral et al, 2002; Kral & Tillein, 2006)…”
Section: Introductionmentioning
confidence: 99%
“…For example, O'Donoghue, Nikolopoulos, and Archbold (2000) reported that 55% of the variance in cochlear implant outcomes is accounted by these two variables together, whereas socioeconomic status of the family and number of inserted electrodes have no significant impact. Data collected both on animals and humans suggest that chronic electrical stimulation may protect the developing auditory system from degeneration and may modify the functional organization of the auditory system (Klinke, Hartmann, Heid, Tillein, & Kral, 2001). Many congenitally deaf children have never had clear, patterned, auditory input; and, thus, they must use degraded input from the cochlear implant to fuel the development of central phonological processing.…”
mentioning
confidence: 99%